KEPASTIAN HUKUM TERHADAP PUTUSAN NOMOR 1025/Pdt.G/2020/PN JKT.SEL MENGENAI KUALITAS KENDARAAN BERMOTOR - Jerry Jerry; Elfrida Ratnawati Gultom (UNES Law Review, 2023)
The quality of motor vehicles, especially cars, is very important when used in various conditions. Car manufacturers/sellers are required to ensure the quality of their products. Consumers as buyers/consumers or users must receive protection from the quality of the products they buy. If the product consumed by consumers has hidden defects, it is appropriate for consumers to be given legal protection, so that in the future there will be no legal problems. Legal certainty regarding consumer protection needs to be understood by consumers, aiming for consumers to have the knowledge to make claims, as well as receive appropriate after-sales service from producers/sellers. Therefore, consumers need to be protected by the positive laws that apply in Indonesia. The law used for consumer protection is the Law of the Republic of Indonesia Number 8 of 1999 concerning Consumer Protection. If there are legal issues related to products that are not suitable for consumption by consumers, consumers have several ways to settle through legal channels, namely through courts or alternative dispute resolution outside the court. So that in the future the relationship between the seller/manufacturer and the buyer/consumer has balance in the eyes of the law, and has legal certainty that can be accounted for.